A dual-database bibliometric analysis of music-based interventions and pain from 2004 to 2024 - Zou, Xianghui; Jin, Ziqi; Zeng, Weiqing (Frontiers in Medicine, 2025)
ObjectivesTo explore the research hotspots and trends in the field of music therapy and pain based on bibliometrics and to provide reference and guidance for the current status and development of research in this field.MethodsUsing the Web of Science Core Collection (WOSCC) and Pubmed databases as data sources, we used VOSviewer and CiteSpace, R language combined, way to visualize and analyze the number of publications, countries, institutions, researchers, keywords, and literature in the fixed field from 2004 to 2024.ResultsPublication volume increased each year, with 2013 having the highest average citation rate. Lead authors included Bradt Joke, Silverman Michael J., Warth Marco, and Kessler Jens. the Journal of Music Therapy ranked first in terms of published papers. The United States leads in research but lacks national collaboration. Research topics have evolved from anxiety, cancer, and pain management to rehabilitation, virtual reality, and quality of life.ConclusionThis study presents a roadmap for optimizing the clinical application of music therapy, addresses gaps in protocol standardization, advocates for cross-national collaboration to improve research quality, and provides important insights and guidance for future music therapy and pain research and applications.